Le vie d’accesso alla scapola - Berlusconi, M. (Lo Scalpello - Journal, 2018)
APPROACHES TO SCAPULA FRACTURES The preoperative plan is very important in the decision of the surgical approach in a fracture of the scapula. To make a good plan we need plan xrays and 3D CT scan. Once we have classified the fracture the approach is very similar to the acetabular approach. In cases in which the main dislocation is in the anterior side of the glenoid, we’ll use a deltopectoral approach. When the main dislocation is in the posterior side, we’ll use the posterior approach. Sometimes the dislocation of the articular fracture is complex and we need a double approach. In this case the decision making will be taken by a 3D scan without the head of the humerus. In this paper we’ll describe the steps of the different approaches.